2006
DOI: 10.1130/b26275.1
|View full text |Cite
|
Sign up to set email alerts
|

The paradox of minibasin subsidence into salt: Clues to the evolution of crustal basins

Abstract: Why do salt-fl oored minibasins subside? An almost universal explanation is that salt is forced from beneath the sinking basin by the weight of its sedimentary fi ll. This explanation is valid if the average density of the basin fi ll exceeds that of salt, which in the Gulf of Mexico needs at least 2300 m of siliciclastic fi ll to ensure enough compaction. However, most minibasins start sinking when they are much thinner than this. Some mechanism other than density inversion must explain the early history of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
183
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(187 citation statements)
references
References 88 publications
3
183
1
Order By: Relevance
“…This ensures that realistic porosities are predicted, essential to a coupled geomechanical/fluid flow analysis. In this case the hardening law of the sediments (which has a first order effect on mechanical compaction) has been calibrated according to a regional compaction trend for Golf of Mexico published in (Hudec et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This ensures that realistic porosities are predicted, essential to a coupled geomechanical/fluid flow analysis. In this case the hardening law of the sediments (which has a first order effect on mechanical compaction) has been calibrated according to a regional compaction trend for Golf of Mexico published in (Hudec et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
“…The hardening law for clay is defined according to a regional compaction trend in Gulf of Mexico by (Hudec et al, 2009) assuming that sediments were are normally pressured. The hardening law for the sand is defined according to a typical sand normal compaction trend.…”
Section: Appendixa1 Materials Propertiesmentioning
confidence: 99%
“…The Late Permian Zechstein salt strongly controlled the Triassic deposition by forming salt withdrawal mini-basins within an overall rift-controlled basinal tectonic setting (Smith et al 1993;Bishop 1996;Matthews et al 2007). The initiation of mini-basin subsidence or creation of salt-walled mini-basins requires the presence of salt with a sufficient thickness to allow halokinesis (Hudec et al 2009), and a mechanism to initiate halokinesis, i.e. extension, compression, differential loading or buoyancy (Banham and Mountney 2013a).…”
Section: Mini-basin Development and Halokinesismentioning
confidence: 99%
“…Such studies have increased our understanding of salt movement, the development of salt-walled mini-basins and on the effects of coeval halokinesis on sedimentary Edited by Jie Hao processes and facies distribution (e.g. Fox 1998;Hudec et al 2009;Banham and Mountney 2013a, b). However, a detailed understanding of the effects of contemporaneous salt movement on diagenesis and reservoir quality is yet to be established.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few experimental and theoretical studies have been conducted to understand the interactions between a depositional body of sediment and a pre-existing, deformable, viscous substrate (Hudec et al 2009;Piliouras et al 2014;Kopriva et al 2015). Each of these studies, however, has revealed the significance of specific variables in controlling the morphology and evolving stratigraphy in experimental settings and how these apply to real world basinal settings.…”
Section: Introductionmentioning
confidence: 99%